Gargalos para transferência de tecnologia: uma análise dos institutos Senai de Inovação em Minas Gerais - Erika Heyden Neves (2018)
This paper aims to analyse what are the main bottlenecks for technology transfer from the Senai Institutes for Innovation from the State of Minas Gerais to companies. Therefore, this study mapped the mechanisms to the transfer of technology that were more usual in the Institutes and companies of their relationship. Based on this identification, we sought to analyze the bottlenecks for the transfer to succeed and which of these are the main ones through the application of questionnaires. Finally, an analysis of these bottlenecks were maid, in order to identify the main ones, to think about ways to solve them or to reduce their impacts.